Albert Watkins and Howard Watkins Family Genealogy Trip to Tennessee - Watkins, Howard::::::::: (1986)
Grave marker of Sara Langston (11/5/1877-7/21/1956); Mother of Rosa Langston Watkins Chattanooga Memorial Park